Ambient ageism: Exploring ageism in acoustic representations of older adults in AgeTech advertisements - Graham, Megan E. (Frontiers in Sociology, 2022)
Ageing-in-place environments are increasingly marked by ambient digital technologies designed to keep older adults safe while they live independently at home. These AgeTech companies market their products by constructing imagined visual and aural worlds of the smart home, usually deploying ageist representations of ageing and older adults. The advertisements are multimodal, and while what is seen on screen is often considered most important in a visuo-centric western culture, scholars have argued that it is what audiences hear that has the greatest impact. The acoustic domain of AgeTech advertisements and its relationship to ageism in marketing has not yet been explored. Accordingly, this paper will address this gap by following Van Leeuwen's framework for critical analysis of musical discourse to explore what AgeTech companies say about ageing, older adults, and ageing-in-place technologies using sound in an illustrative set of smart home advertisements for ageing-in-place. The paper will discuss how music, voice, and sound are semiotic resources that are used to construct stereotypical (both negative and positive) portrayals of older adults, reinforce the narrative of “technology as saviour,” and trouble the private/public boundaries of the ageing-in-place smart home.